Financial Resources of the Decentralized Autonomous Governments: Case Study Autonomous Decentralized Municipal Governments - Dávila, María José (2018)
The better management of the different levels of government, in which there is a direct relationship with citizens, led to a new model of assuming and executing competencies. Decentralization brought a different distribution of resources based on the characteristics of the territory and on equity, but it also left a continuous work that the Decentralized Autonomous Governments (GAD) must carry out to strengthen their institutional and financial capacities. Hence the importance of strengthening the finances of the GAD through its management with a focus on its main own income. The quantitative analysis based on the municipal GAD states that although it is true that in the period between 2006-2015 its income has increased and the dependency index has been gradually decreasing, however this decrease is short, because the index is located in 77%. Undoubtedly, the management by the municipal GADs in strengthening their finances has resulted in an increase in collection for their main own income, that is, taxes (property tax, patents and total assets), reaching a greater representation in relation to gross domestic product (GDP).